Age is Nothing but a Number: Ben 10s, Sugar Mummies, and the South African Gender Order in the Daily Sun’s Facebook Page - Boshoff, Priscilla; Mlangeni, Ntombi Lina (Frontiers in Sociology, 2021)
Stories about “Ben10” relationships between older women and their younger male lovers appear regularly in the Daily Sun, South Africa’s most popular tabloid newspaper. Daily Sun readers, who are typically township residents, engage vociferously over the rights and wrongs of such relationships on the tabloid’s Facebook page, and alternatively berate or support the older, working class women who feature in them. These women could be understood as “postfeminist” insofar as they are financially independent and sexually autonomous. Their actions echo those of the independent township women in the mid twentieth century who, resisting patriarchal apartheid social engineering, brewed beer and rented rooms in order to assert their financial and sexual independence. In both cases, these women’s bold actions confront local hetero-patriarchal norms and call into question an ideal local patriarchal gender order. However, the meanings that are made by the readers of such women in Ben10 relationships today also reflect a social context characterised by a contestation over the meaning of rights, high rates of unemployment, gender-based violence and HIV, factors that curtail a premature diagnosis of postfeminist identity. Drawing on a textual analysis of several articles and their Facebook comments, we argue that any assessment of postfeminism in southern spaces must account for how historical and contextual factors such as these constrain the reach of global postfeminism.